Azospirillum spp. Isolated from Raigarh District of Chhattisgarh - Swati Rosh Ekka2, Preeti Tiwari1, Jaya Tripathi2 and (Journal of Phytology, 2011)
Azospirillum is considered the most important rhizobacterial genus for improvement of plant growth or crop yield worldwide. They are potential N2 fixer, associated closely with roots and rhizospheres of many economically important plants and grasses. By the help of soil dilution technique and Root tip cuttings we can isolate these bacteria. 25 soil samples were collected from Raigarh district of Chhattisgarh and 25 different bacterial cultures were isolated out of which 4 cultures are Azospirillum and rest 20 culture are identified as Bacillus subtilis and 1 as Streptococcus spp. All 4 are gram negative in nature.Ã‚Â These all are growth plant promoting bacteria and play a beneficial role on crop productivity by fixing atmospheric nitrogen, solubilising unavailable phosphates, decomposing organic wastes and enhance nutrient recycling by producing bioactive substances such as vitamins, hormones, enzymes etc. Azospirillum can fix nitrogen biologically in to the soil thus are beneficial for environment.